A comparison of expressed emotion between mothers and their adolescent daughters with and without a history of nonsuicidal self-injury - Taru Tschan; Simone Pfeiffer; Raphael Gutzweiler; Tina In-Albon (BMC, 2022)
Abstract Background Expressed Emotion refers to the extent to which close relatives express critical/hostile and/or emotionally overinvolved attitudes and feelings when speaking about a family member. High Expressed Emotion is a valuable predictor of clinical outcomes and is related to the presence of various mental disorders, including nonsuicidal self-injury (NSSI). Interpersonal factors have been shown to be relevant in initiating and in maintaining with NSSI, as interpersonal difficulties are often reported as triggers for emotional dysregulation. The parental role in the etiology and treatment of NSSI needs to be further investigated. This study assesses Expressed Emotion in adolescents who engage in NSSI and their mothers. Method We examined Expressed Emotion levels of mother-daughter dyads among adolescents who engage in NSSI, clinical controls (CCs), and nonclinical controls (NCs). The sample consisted of 70 female adolescents aged 12-20 years (M = 15.28 years, SD = 1.81; NSSI: n = 21, CC: n = 17, NC: n = 32) and 24 mothers aged 38-56 years (M = 46.47 years, SD = 4.61) using The Five-Minute Speech Sample (FMSS). Results Adolescents who engage in NSSI exhibited significantly more covert criticism and critical tone toward their mothers than CCs (d = 0.65, d = 1.10) and NCs (d = 1.30, d = 1.10). Conclusion The findings highlight the importance of family-based interventions for the treatment of NSSI in order to enhance a positive relationship quality between parents and adolescents.